What drives financial performance–resource efficiency or resource slack? - Modi, Sachin B.; Mishra, Saurabh (Journal of Operations Management, 2011)
AbstractExtant research in operations management has revealed divergent insights into the value potential of resource efficiency. While one view relates efficiency with good operations management and asserts that slack resources are a form of waste that should be minimized, the other view suggests that limited resource slack can impose heavy costs on firms by making them brittle. In this research, the authors build on these views to investigate the relationship of inventory, production, and marketing resource efficiency of firms with three metrics of financial performance (i.e., Stock‐Returns, Tobin's Q, and Returns‐on‐Assets). The authors evaluate the theoretical framework using secondary information on all U.S. based publicly‐owned manufacturing firms across the 16‐year time period of 1991–2006. Analysis utilizing a mixed‐model approach reveals that a focus on resource efficiency is positively associated with firm financial performance. However, findings also support the arguments favoring slack, indicating that the financial gains from resource efficiency exhibit diminishing returns.